An interesting case report of ruptured pyogenic liver abscess with 40 weeks gestation in labour - Mevada, Shraddha A.; Bhosale, Archana A.; Wankhedkar, Sayali; Choudhari, Rucha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Pyogenic liver abscess during pregnancy is an extremely rare condition. Although rare, in situations of sepsis or septic shock in pregnancy, as well as the common sources of infection, a possibility of a liver abscess should be considered. We present a case report of 32-year-old primigravida 37.3 weeks by date, 37 weeks by scan with breech presentation with premature rupture of membranes and pain in abdomen since 12 hours with breathlessness, fever and diarrhoea since 2 days came in emergency to study hospital. General condition of the patient on arrival was pulse-140 beats per minute, blood pressure was 90/60 mmHg, respiratory rate was 40/min, on per abdominal examination, breech presentation with fetal heart rate of 150 beats per minute on doppler was noted. Per vaginal examination revealed cervical os 5 cm dilated, 40% effacement, breech presentation, absent membranes. With urgent report of complete hemogram and acid blood gas analysis, metabolic acidosis was noted which was corrected and patient was taken for emergency lower segment caesarean section. Intra-operative, 250 ml greenish pus flakes fluid was noted inside the abdominal cavity. Fluid was drained and sent for culture sensitivity with maximum aseptic precautions, uterus was opened, baby was delivered followed by uterus closure. Ruptured liver abscess 6×4×2 cm in 2nd and 3rd segment of liver was noted, abdominal wash with antibiotics and NS was given, drain was kept. Appropriate antibiotics were started and was discharged on day 14 after suture removal.